Konsep Keuangan Publik Islam Abu ‘Ubaid al-Qasim bin Salam dalam Implementasi Kebijakan Fiskal Berbasis Zakat di Indonesia - Vina Fitria; Salsabila Salsabila; Lina Marlina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the concept of Islamic public finance according to Abu 'Ubaid al-Qasim bin Salam in Kitab al-Amwal and its relevance to the implementation of zakat-based fiscal policy in Indonesia. Using a qualitative approach and library research method, the study reveals that Abu 'Ubaid emphasized three main principles in public finance management: justice, transparency, and public benefit (maslahah). He viewed zakat as a public financial instrument that must be managed by the state to ensure fair and equitable distribution of wealth. The implementation of zakat-based fiscal policy in Indonesia still faces challenges such as low public awareness, lack of integration into the national and regional budgets, and uneven zakat distribution. Based on Abu ‘Ubaid's thoughts, the proposed solutions include strengthening regulations, improving transparency in zakat institutions, and optimizing the use of technology. Integrating zakat into the public financial system can be an effective strategy to reduce social inequality and promote sustainable public welfare.